Analisis Kadar Air, Keasaman, dan Gula Reduksi Madu Budidaya secara kimiawi - Siska Rusmalina; Kharismatul Khasanah; Annisatul Farokhah; Dwiki Abdul Mutholi (An-Najat, 2024)
. Honey is a sticky, sweet liquid produced by bees or other insects from flower nectar. It has a distinct flavor compared to sugar and sweeteners, varying based on the plant source. Government-established quality standards protect consumers, ensure fair trade, and align with current regulations and technologies. This study aims to assess the quality of cultivated pure honey through organoleptic evaluation, water content analysis, acidity testing, and reducing sugar content analysis. Using a descriptive observational method and random sampling, samples from different honey types and brands were selected. Quantitative analysis determined water content using an oven-drying method, acidity using acid-base neutralization, and reducing sugar content using the iodometric method with Luff Schoorl reagent, following SNI 8664-2018 requirements. The study found varying organoleptic characteristics among different brands due to differences in bee species, floral sources, and production locations. Among the 18 samples tested, 10 met the water content standard, 14 met the acidity standard, but none met the reducing sugar content standard, indicating overall non-compliance with all requirements.